Law Enforcement Against Political Crimes in Elections - Nur Fadhliyah Putri Daud; Zamroni Abdussama (Estudiante Law Journal, 2022)
: This study aims to determine law enforcement against political crimes in elections. The method used in this study is research methodology The type of research used is sociological juridical and this study uses a descriptive research approach and quality data analysis techniques. The results of this study show that law enforcement against political crimes within the scope of the 2019 legislative elections in Boalemo Regency has not been carried out optimally. Where from the series of cases that have been described in the discussion which amounts to 7 cases, what can be solved by Bawaslu is only 2 cases. So that it can provide an understanding that law enforcement against election violations by Bawaslu is still not implemented properly, even though there are already regulations that regulate it. Supervision of political money should be Bawaslu increased Supervision in the form of participatory supervision.